THE USE OF DOCUMENTARY FILMS AS A HISTORY TEACHING MEDIUM FOR 11TH GRADE STUDENTS AT MADANI PALU INTEGRATED MODEL HIGH SCHOOL - Nur Fadila S; Haliadi Sadi; Priyatna Prasetyawati; Windayanti (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study investigates the implementation of documentary films as instructional media in history education by examining their pedagogical contributions, the challenges encountered during implementation, and their implications for improving the quality of history learning. A qualitative descriptive approach was employed, with data collected through classroom observations, in-depth interviews, and documentation. Purposive sampling was used to select one history teacher and six Grade XI students at SMAN Model Terpadu Madani Palu who had direct experience with documentary film-based instruction. The findings reveal that documentary films significantly enhanced students’ learning motivation, classroom participation, concentration, and understanding of historical concepts by providing authentic visual representations that facilitated comprehension of historical chronology and context. The integration of documentary films also promoted a more interactive and student-centered learning environment through reflective classroom discussions. Nevertheless, several implementation challenges were identified, including limited instructional facilities, unstable internet connectivity, classroom noise, and the lengthy duration of documentary films, all of which affected instructional effectiveness. These findings suggest that documentary films represent an effective pedagogical tool for history education by fostering meaningful learning experiences and strengthening students’ cognitive engagement with historical content. The study further highlights the importance of adequate technological infrastructure and careful instructional planning to optimize the integration of documentary films into history teaching.